A Sulfur‐Tolerant MOF‐Based Single‐Atom Fe Catalyst for Efficient Oxidation of NO and Hg0 (Adv. Mater. 20/2022). Issue 20 (19th May 2022) - Yang, Weijie; Liu, Xiaoshuo; Chen, Xuelu; Cao, Yue; Cui, Shaoping; Jiao, Long; Wu, Chongchong; Chen, Chuanmin; Fu, Dong; Gates, Ian D.; Gao, Zhengyang; Jiang, Hai‐Long
Abstract : Single‐Atom Catalysts A single‐atom Fe decorated N‐doped carbon catalyst (Fe1 ‐N4 ‐C), derived from an Fe‐doped metal–organic framework, is developed by Zhengyang Gao, Hai‐Long Jiang, and co‐workers in article number 2110123 . The unique Fe1 ‐N4 sites in Fe1 ‐N4 ‐C enable ultrahigh activity for catalytic oxidations of NO and Hg(0) at low and room temperature. The preferable adsorption of reactants enables Fe1 ‐N4 ‐C robust sulfur resistance.